Optical conductivity in an effective model for graphene: finite temperature corrections (015401) - Falomir, Horacio Alberto (2019)
In this article, we investigate the temperature and chemical potential dependence of the optical conductivity of graphene, within a field theoretical representation in the continuum approximation, arising from an underlying tight-binding atomistic model, that includes up to second-nearest neighbors coupling. Our calculations allow us to obtain the dependence of the optical conductivity on frequency, temperature and finite chemical potential, thus generalizing our previously reported calculations at zero temperature, and reproducing the universal and experimentally verified value at zero frequency. Moreover, we also show that a small but still measurable shift in the conductance minimum arises as a function of the second-nearest neighbors hopping t´, thus providing the possibility to directly measure this parameter in transport experiments.